Penerapan Teknologi Budikdamber untuk Meningkatkan Ketahanan Pangan Rumah Tangga di Desa Plemahan, Jombang - Moh. Faridl Darmawan; Yessita Puspaningrum; Septian Ragil Anandita; Muchammad Faruq Almuzaqqi; Muhammad Miftachul Amri; Alvin Rosyid Auwaliansyah; M. Wahyu Dwi Iqbal Bachtiar (Jumat Pertanian: Jurnal Pengabdian Masyarakat, 2026)
The limitation of agricultural land and the reliance on conventional farming systems have placed food security in Plemahan Village, Sumobito District, Jombang Regency in a vulnerable condition. This community service program introduced the Fish Cultivation in Buckets (Budikdamber) method, which integrates fish farming with vegetable cultivation in simple containers. The program aimed to improve community skills in managing small-scale integrated farming systems, to foster awareness of food self-sufficiency, and to establish new social practices based on agricultural innovation. The method applied was Participatory Action Research, consisting of socialization, technical training, mentoring, and evaluation. The results indicated that participants improved their skills in managing fish and vegetable cultivation, developed new habits of utilizing household yards, and witnessed the emergence of local leaders supporting program sustainability. This program demonstrates that simple agricultural innovations can serve as an effective means of enhancing food security while promoting social transformation at the community level.